Manganese-Based Bifunctional as an Oil–Soluble Homogenous Catalyst for in–Situ Catalytic Upgrading of High Sulfur Heavy Crude Oil - AL-Mishaal, Omar F.; Hussein, Atta O.; Issa, Taha A. (Journal of Petroleum Research and Studies, 2025)
Manganese naphthenate (C₂₂H₁₄MnO₄), a black oil-soluble liquid, was used for the first time as a bifunctional homogeneous catalyst in heavy oil upgrading under steam conditions. The catalyst combines two key functions: cracking, due to the 6% manganese content, and hydrogen donation from the naphthenate component, which enhances hydrogenation reactions, increases the H/C ratio, and facilitates hydrodesulfurization. Experiments were conducted in an autoclave reactor using heavy oil with high sulfur content under three temperatures (200, 250, and 300 °C) for 24 hours, in the presence and absence of the catalyst. The study employed several analytical techniques—viscosity measurement, SARA analysis, gas chromatography (GC), and X-ray diffraction (XRD)—to evaluate catalyst performance. Gas analysis by GC showed that, without the catalyst, the total light hydrocarbon gases (ΣC₁–C₄) and H₂S reached 0.8150 wt% and 1.2960 wt%, respectively, while with the catalyst, these increased to 1.4905 wt% and 1.5400 wt%. This indicates enhanced cracking and desulfurization activity. Viscosity measurements using a Brookfield Viscometer revealed that at 300 °C, the catalyst reduced the oil viscosity from 2802 mPa·s to 1437 mPa·s, achieving a 51% reduction, compared to only 29% (to 1962 mPa·s) without the catalyst. SARA analysis showed that the light fractions (saturates + aromatics) increased from 72% in the original oil to 80.76% with the catalyst and 75.69% without it, confirming significant cracking and hydrogenation. The presence of MnS in the solid residues after reaction further supports the catalyst’s participation in hydrodesulfurization. Overall, manganese naphthenate demonstrated excellent catalytic activity in upgrading heavy oil through combined cracking, hydrogenation, and desulfurization mechanisms under steam conditions, making it a promising candidate for improving the quality and flow properties of high-sulfur heavy crude oils.